Enflicoxib for the long-term management of canine osteoarthritis—External validation of a population pharmacokinetic model in dogs with osteoarthritis - Cendrós, Josep-Maria; Salichs, Marta; Encina, Gregorio; Vela, Jose Miguel; Homedes, Josep (Frontiers in Veterinary Science, 2025)
IntroductionEnflicoxib is a cyclooxygenase-2 (Cox-2) selective non-steroidal anti-inflammatory drug (NSAID) indicated for the treatment of pain and inflammation in canine osteoarthritis (OA) and in soft and orthopedic surgery. Canine OA is a chronic progressive disease that requires long-term therapy.MethodsThe suitability of enflicoxib for its long-term use was assessed by analyzing the concentrations determined in plasma samples from dogs included in a field clinical study using a previously established population pharmacokinetic (popPK) model. One hundred and nine client-owned dogs with OA of different breeds, ages, and weights were enrolled and treated with enflicoxib weekly for 6 months at the recommended dose. Safety was assessed clinically and by repeated blood and urine analysis. Two plasma samples were obtained from 83 dogs that received at least one enflicoxib dose. Concentrations of enflicoxib and its pyrazol metabolite were determined, modeled, and compared with the predictions of the previously established popPK model in healthy Beagle dogs.ResultsEnflicoxib and pyrazol metabolite plasma levels could be adequately predicted by the established popPK model. No covariates other than body weight had any influence on the PK parameters. No over-accumulation of either compound was observed.DiscussionThe established popPK model in healthy Beagle dogs can predict the PK behavior of enflicoxib and its pyrazol metabolite in dogs of any breed with OA. The lack of time-dependent PK provides a PK rationale to support continuous enflicoxib treatment for as long as therapeutically required.